2019
DOI: 10.1111/nph.16236
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between REVEILLE1 and RGA‐LIKE2 regulates seed dormancy and germination in Arabidopsis

Abstract: Environmental light signal and GAs synergistically regulate seed dormancy and germination. The phytochrome B (phyB) photoreceptor regulates expression of the REVEILLE1 (RVE1) transcription factor, which directly inhibits GIBBERELLIN 3-OXIDASE2 transcription, suppressing GA biosynthesis. However, whether phyB-RVE1 coordinates with GA signaling in controlling seed dormancy and germination remains unknown.Here, we demonstrate that RVE1 regulation of seed dormancy and germination requires a DELLA repressor, REPRES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…Furthermore, RVE1 stabilizes a DELLA protein RGA-LIKE2 (RGL2) to depress seed germination and enhance seed dormancy. Meanwhile, RGL2 could enhance the transcriptional activity of RVE1 during seed dormancy and germination (Yang et al 2020). As described above, we summarize that PIF1 and RVE1 play key roles in light-mediated seed germination, and that they could be regulated by other factors.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…Furthermore, RVE1 stabilizes a DELLA protein RGA-LIKE2 (RGL2) to depress seed germination and enhance seed dormancy. Meanwhile, RGL2 could enhance the transcriptional activity of RVE1 during seed dormancy and germination (Yang et al 2020). As described above, we summarize that PIF1 and RVE1 play key roles in light-mediated seed germination, and that they could be regulated by other factors.…”
Section: Introductionsupporting
confidence: 57%
“…Similarly, RVE1 enhances the DNA-binding capacity (and may enhance transcriptional activity) on ABI3 expression by PIF1 ( Figure 5). We previously showed that RGL2 also accelerates the DNA-binding ability and transcriptional activity of RVE1 in regulating GA3ox2 expression (Yang et al 2020). LEUNIG_HOMOLOG interacts with PIF1 and functions as a transcriptional coregulator to inhibit seed germination (Lee et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ABI4 is a key transcription factor that can be directly or indirectly involved in the regulation of key genes in the ABA and GA biogenesis pathways leading to seed dormancy [9]. The transcription factor REVEILLE1 (RVE1) interacts with REPRESSOR OF GA-LIKE2 (RGL2) to regulate the dormancy and germination of Arabidopsis thaliana seeds by integrating light perception, GA metabolism and the associated signalling pathways [10]. In the process of GAmediated promotion of seed germination, GA3ox1 and GA3ox2 are two key genes regulating GA synthesis [11], while GA2ox promotes GA degradation [12].…”
Section: Introductionmentioning
confidence: 99%